Swarming Responsive Photonic Nanorobots for Motile-Targeting Microenvironmental Mapping and Mapping-Guided Photothermal Treatment - Li, Luolin; Yu, Zheng; Liu, Jianfeng; Yang, Manyi; Shi, Gongpu; Feng, Ziqi; Luo, Wei; Ma, Huiru; Guan, Jianguo; Mou, Fangzhi (Nano-micro letters, 2023)
Highlights Responsive photonic nanorobots (RPNRs) simultaneously exhibit energetic magnetically-propelled swarming motions, bright stimuli-responsive structural colors, and photothermal conversion. The swarming RPNRs can actively navigate in complex environments and collectively map out local physicochemical conditions (e.g., pH, temperature, or glucose concentration) on the fly via their bright responsive structural colors. The swarming RPNRs can visualize an unknown target (e.g., tumor lesion) via motile-targeting mapping and then guide the external NIR light to initiate localized photothermal treatment. Micro/nanorobots can propel and navigate in many hard-to-reach biological environments, and thus may bring revolutionary changes to biomedical research and applications. However, current MNRs lack the capability to collectively perceive and report physicochemical changes in unknown microenvironments. Here we propose to develop swarming responsive photonic nanorobots that can map local physicochemical conditions on the fly and further guide localized photothermal treatment. The RPNRs consist of a photonic nanochain of periodically-assembled magnetic Fe 3 O 4 nanoparticles encapsulated in a responsive hydrogel shell, and show multiple integrated functions, including energetic magnetically-driven swarming motions, bright stimuli-responsive structural colors, and photothermal conversion. Thus, they can actively navigate in complex environments utilizing their controllable swarming motions, then visualize unknown targets (e.g., tumor lesion) by collectively mapping out local abnormal physicochemical conditions (e.g., pH, temperature, or glucose concentration) via their responsive structural colors, and further guide external light irradiation to initiate localized photothermal treatment. This work facilitates the development of intelligent motile nanosensors and versatile multifunctional nanotheranostics for cancer and inflammatory diseases.